SOIL SALINIZATION AND ITS EFFECTS ON MORPHO-PHYSIOLOGICAL CHARACTERISTICS OF SUGARCANE VARIETIES - Targino, Herbert Cayque Oliveira; da Silva, José Aliçandro Bezerra; da Silva, Edson Pereira; Amorim, Magno do Nascimento; Seabra, Tales Xavier (Revista Geama, 2017)
Brazil is one of the world’s largest sugarcane producers, and its cultivation has extreme economic importance. The Sub-Mid São Francisco Valley region presents high sugarcane yield indexes, but this region also has areas with high salinity levels. Thus, the objective of this study was to evaluate the effects of salinity on the growth and development of commercial varieties of sugarcane. The experiment was conducted in a nursery, located in the Federal University of the São Francisco Valley, Juazeiro, in the state of Bahia, Brazil. Three commercial varieties of sugarcane—VAT-90212, RB-92579, and SP-791011—were cultivated under two types of soil from areas owned by the agroindustry Agrovale. One of the soils had electrical conductivity (EC) of 4.6 dS.m -1 (saline), and the other had EC of 1.5 dS.m -1 (non-saline). Morphological parameters determining the plant growth and development, leaf chlorophyll content, and gas exchange were evaluated. The results presented that the salinity decreased the morphological parameters of all the evaluated sugarcane varieties. A similar result was found for photosynthetic activity and chlorophyll content.